2018
DOI: 10.29364/epsy.318
|View full text |Cite
|
Sign up to set email alerts
|

Škála vytrvalosti: Analýza psychometrických vlastností české verze pro dospělé

Abstract: The aim of this study is to test the psychometric properties of Czech adaptation of 8-item Short Grit Scale based on item analysis, internal consistency, content and convergent validity. The sample of 338 respondents included 209 (61.8 %) female and 129 (38.2 %) male participants between 15 and 76 years of age (M = 28.39; sd = 10.5). The results suggest satisfactory reliability and validity. Comparative analyses of demographic factors (age and gender) revealed a significant positive relationship between age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Except of EntreComp questionnaire, the following measures were used as validation methods:  Grit (Duckworth & Quinn, 2009;Kropáčová, S., Slezáčková, & Jarden, 2018);  General self-efficacy scale (Košč, Heftyová, Schwarzer, & Jerusalem, 1993);  Brief Self-control Scale (Tangney, Baumeister, & Boone, 2004);  Motivation (Sheldon, & Elliot, 1999);  DOSPERT -Domain-Specific Risk-Taking (Blais & Weber, 2006);  TEIQue -Trait Emotional Intelligence Questionnaire (Kaliská, Nábělková, & Salbot, 2015;Petrides, & Furnham, 2009);  NEO FFI -Five-factor personality inventory (McCrae & Costa, 2004;Ruisel, & Halama, 2007);  Short Dark Triad Scale (Čopková & Šafár, 2021;Jones & Paulhus, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Except of EntreComp questionnaire, the following measures were used as validation methods:  Grit (Duckworth & Quinn, 2009;Kropáčová, S., Slezáčková, & Jarden, 2018);  General self-efficacy scale (Košč, Heftyová, Schwarzer, & Jerusalem, 1993);  Brief Self-control Scale (Tangney, Baumeister, & Boone, 2004);  Motivation (Sheldon, & Elliot, 1999);  DOSPERT -Domain-Specific Risk-Taking (Blais & Weber, 2006);  TEIQue -Trait Emotional Intelligence Questionnaire (Kaliská, Nábělková, & Salbot, 2015;Petrides, & Furnham, 2009);  NEO FFI -Five-factor personality inventory (McCrae & Costa, 2004;Ruisel, & Halama, 2007);  Short Dark Triad Scale (Čopková & Šafár, 2021;Jones & Paulhus, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Grit-S. The translated version of the eight-item Grit-S (Duckworth & Quinn, 2009) was used to assess grit (Kropáčová, Slezáčková, & Jarden, 2018), with four items measuring each facet (see Table 1). The response format ranged from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Confirmatory factor analyses showed that the Grit-S fit data better than the Grit-O, and the predictive validity had not decreased even though there were fewer items, that is, the Grit-S was a more efficient grit measure. Consequently, the Grit-S was translated into many languages, including Korean [11], Japanese [12], Turkish [13,14], German [15], Polish [16], Italian [17], Spanish [18,19], Czech [20,21], Chinese [22][23][24], Arabic [25], and Portuguese [26].…”
Section: Introductionmentioning
confidence: 99%